Power and Metaphor - Rémi Digonnet (Lexis: Journal in English Lexicology, 2014)
Through the study of various American presidents’ inaugural addresses, from F.D. Roosevelt’s first address to B. Obama’s second inaugural address, the powers of metaphor, either ornamental, cognitive, or political, will be highlighted before a thorough analysis of the metaphors of power, whether they be collective (military metaphors, architectural metaphors), individual (the president as the father, the master, the surgeon), or even divine. Conjointly taking metaphor and power into consideration will eventually help answer the following question: do power metaphors reflect the increasing executive powers conferred on the president over this period?